"Exercise to be fit, not skinny": The effect of fitspiration imagery on women's body image. (September 2015) - Tiggemann, Marika; Zaccardo, Mia
Highlights: Fitspiration images have a positive effect on motivation to pursue healthy goals. Fitspiration images have a negative effect on body image. Negative effect on body image is mediated by appearance-based social comparison. Abstract: Fitspiration is an online trend designed to inspire viewers towards a healthier lifestyle by promoting exercise and healthy food. The present study aimed to experimentally investigate the impact of fitspiration images on women's body image. Participants were 130 female undergraduate students who were randomly assigned to view either a set of Instagram fitspiration images or a control set of travel images presented on an iPad. Results showed that acute exposure to fitspiration images led to increased negative mood and body dissatisfaction and decreased state appearance self-esteem relative to travel images. Importantly, regression analyses showed that the effects of image type were mediated by state appearance comparison. Thus it was concluded that fitspiration can have negative unintended consequences for body image. The results offer support to general sociocultural models of media effects on body image, and extend these to "new" media.